A Simplified method to minimize exterior girder rotation of steel bridges during deck construction. (15th March 2019) - Hui, Li; Hraib, Faress; Gillis, Brandon; Vicente, Miguel; Hindi, Riyadh
Highlights: More than four thousand finite element models are built by varying bridge geometries. Stepwise variable selection method is used to remove the redundant parameters. Effects of bridge geometrical parameters are inspected. Three regression models are developed and compared. A simplified method for determining the B/D ratio is developed and validated. Abstract: Wide flange beams are widely used in the United States for bridge design and construction. During the overhang construction of the bridge, torsional loads are often induced due to the fresh concrete load and the use of a deck finishing machine located on the overhang formwork. These torsional moments sometimes cause excessive exterior girder rotation, resulting in many safety and maintenance issues during the construction and service stages. To prevent these issues, most states have specifications for limiting the rotation. Finite element analysis using shell or solid elements is usually recommended for analyzing bridge girders in overhang construction, which can be tedious and difficult in some cases. This study focused on developing a simple method with minimal calculation to evaluate the ratio of unbraced length to girder depth (B/D ratio). The stepwise variable selection method and a regression analysis were conducted to find the relationship between the exterior girder rotation and bridge geometries. A computer program for automatic finite element modeling in SAP2000 was developed using MATLAB, resulting in 4285 finite element models with different bridge geometries being developed to generate artificial data. By conducting a study of variable selection, three parameters were selected based on level of significance. After conducting a regression analysis based on the selected parameters, a method using the normal weight of girder, overhang width, and rotation limit to determine B/D ratio was developed.